Comparison of the epidemiological profile of congenital syphilis in the Northeast and Southeast regions of Brazil from 2017 to 2019 (Research, Society and Development, 2021)
Despite being treatable, congenital syphilis infection in Brazil is extremely high. Thus, the objective of this work is to compare the epidemiological profile of congenital syphilis in the Northeast and Southeast regions of Brazil between the years 2017 to 2019. This research is an epidemiological, descriptive and retrospective research, data collection was selected through consultation electronic to the data contained in the DATASUS platform, in the Notifiable Diseases Information System (SINAN) between the years 2017 to 2019. As a result, 11,824 cases of congenital syphilis were reported in 2019 in Brazil. In the last three years, 27 158 cases of syphilis in children under one year of age were registered in the Southeast region and 18017 in the Northeast region. Deficiencies in the prenatal support offered to pregnant women with inadequate treatment for them and their partners were evidenced, essential requirements to avoid vertical transmission. However, despite still showing high rates of contagion, the number of cases dropped from 2017 to 2019 in both regions.